Glacier inventory Stubai Alps 2017/2018 - Helfricht, Kay; Hartl, Lea; Stocker-Waldhuber, Martin; Seiser, Bernd; Fischer, Andrea (PANGAEA, 2025)
The glacier inventory data set includes the shape file of glacier outlines for the Stubai Alps /Tyrol/Austria) for the year 2017 or 2018, depending on the time of the LiDAR data acquisition. The glacier outlines were delineated manually by editing the features of the 3rd Austrian glacier inventory (GI3) based on high resolution LiDAR data and orthophotos (Abermann et al., 2009), both acquired by the Federal Administrations of Tyrol between June 19, 2017 and July 31, 2018. The 117 glaciers of the Stubai Alps cover 37.4±1.1 km² in 2017/18, which is only 34±2% of their LIA extent of 110.1±11.0 km² (Fischer et al., 2015). The glacier area decreased by 23±0.5% since 2006 (GI3). This data set will be added to a new glacier inventory for Austria (proposed GI5) once updates for all glacier regions of Austria become available from high resolution digital elevation models.
Keywords: Alps; Glacier inventory; Glaciers_austria; LiDAR DEM